2009
DOI: 10.1523/jneurosci.3888-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Rod Phototransduction Determines the Trade-Off of Temporal Integration and Speed of Vision in Dark-Adapted Toads

Abstract: Human vision is ϳ10 times less sensitive than toad vision on a cool night. Here, we investigate (1) how far differences in the capacity for temporal integration underlie such differences in sensitivity and (2) whether the response kinetics of the rod photoreceptors can explain temporal integration at the behavioral level. The toad was studied as a model that allows experimentation at different body temperatures. Sensitivity, integration time, and temporal accuracy of vision were measured psychophysically by re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…An average unperturbed TTP of rods at 36°C of 147 ms falls in the middle of previously reported values for mammalian rods at body temperature (macaque/patch: 200–218 ms in Schneeweis & Schnapf, 1995, 2000; macaque/suction pipette: 190 ms in Baylor et al 1984; human/suction pipette: 189 ms in Kraft et al 1993; mouse/suction pipette: 104 ms in Burns et al 2002; 180 ms in Nikonov et al 2005, 2006; 218 ms in Dunn et al 2006; 181 in Azevedo & Rieke, 2011; mouse, rat/ in vitro ERG: 150 in Nymark et al 2005; 120–130 in Vinberg et al 2009). There is significant divergence in the literature regarding cone kinetics (reviewed in Haldin et al 2009), but recent suction pipette (Nikonov et al 2006) and in vitro ERG recordings (Heikkinen et al 2008) reported a TTP of ∼50 ms for mouse cones at body temperature, in line with our present estimate with patch clamp. It must be noted that the possible presence of a gap junction‐mediated rod component in our cone recordings (see below) may have influenced our measurements of cone TTP.…”
mentioning
confidence: 41%
“…An average unperturbed TTP of rods at 36°C of 147 ms falls in the middle of previously reported values for mammalian rods at body temperature (macaque/patch: 200–218 ms in Schneeweis & Schnapf, 1995, 2000; macaque/suction pipette: 190 ms in Baylor et al 1984; human/suction pipette: 189 ms in Kraft et al 1993; mouse/suction pipette: 104 ms in Burns et al 2002; 180 ms in Nikonov et al 2005, 2006; 218 ms in Dunn et al 2006; 181 in Azevedo & Rieke, 2011; mouse, rat/ in vitro ERG: 150 in Nymark et al 2005; 120–130 in Vinberg et al 2009). There is significant divergence in the literature regarding cone kinetics (reviewed in Haldin et al 2009), but recent suction pipette (Nikonov et al 2006) and in vitro ERG recordings (Heikkinen et al 2008) reported a TTP of ∼50 ms for mouse cones at body temperature, in line with our present estimate with patch clamp. It must be noted that the possible presence of a gap junction‐mediated rod component in our cone recordings (see below) may have influenced our measurements of cone TTP.…”
mentioning
confidence: 41%
“…Given the slow response kinetics of vertebrate rods at low temperatures (Nymark et al, 2005), the visual latency of species A may be shorter by several seconds compared with that of species B (cf. Aho et al, 1993;Haldin et al, 2009).…”
Section: Functional Correlates: Contrast Sensitivity Visual Range mentioning
confidence: 99%
“…The neural images in the toads' eyes and the spiders' motionless secondary eyes are assumed to adapt to stationary surroundings, and only moving objects would pop up on the animals' retinae (Ewert and Borchers, 1974;Land and Barth, 1992). Toad rod photoreceptor cells have integration times of 1.0-1.3s at 25°C, and substantially longer integration times at lower temperatures (Haldin et al, 2009) and are thus roughly 10 times slower than photoreceptors in C. salei. A good match was found between the integration time of the toad rod photoreceptor cells at different temperatures and the 'exposure time' of a dummy necessary to elicit prey capture (Haldin et al, 2009).…”
mentioning
confidence: 99%
“…Toad rod photoreceptor cells have integration times of 1.0-1.3s at 25°C, and substantially longer integration times at lower temperatures (Haldin et al, 2009) and are thus roughly 10 times slower than photoreceptors in C. salei. A good match was found between the integration time of the toad rod photoreceptor cells at different temperatures and the 'exposure time' of a dummy necessary to elicit prey capture (Haldin et al, 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation